Failure Prediction in Underground Mine Excavations Using the Combination of Critical Strain and Ground Reaction Curve (Grc) for the Purpose of Appropriate Support Type and Installation Time - Masoudi, Reza (Curtin University, 2019)
In this Research, a ground reinforcement design method introduced that facilitates the selection of a suitable reinforcement system using the estimation of ground energy demand and measurement of rockbolts energy dissipation capacities and guides the designer to adjust it based on observed ground and support reaction. Rock bolt dynamic tests under single and multiple impacts simulating seismic mining conditions improved the knowledge of bolt behaviour under those conditions.